The General Anesthetic Isoflurane Bilaterally Modulates Neuronal Excitability - Ou, Mengchan; Zhao, Wenling; Liu, Jin; Liang, Peng; Huang, Han; Yu, Hai; Zhu, Tao; Zhou, Cheng (iScience, 2020)
Volatile anesthetics induce hyperactivity during induction while producing anesthesia at higher concentrations. They also bidirectionally modulate many neuronal functions. However, the neuronal mechanism is unclear. The effects of isoflurane on sodium channel currents were analyzed in acute mouse brain slices, including sodium leak (NALCN) currents and voltage-gated sodium channels (Nav) currents. Isoflurane at sub-anesthetic concentrations increased the spontaneous firing rate of CA3 pyramidal neurons, whereas anesthetic concentrations of isoflurane decreased the firing rate. Isoflurane at sub-anesthetic concentrations enhanced NALCN conductance but minimally inhibited Nav currents. Isoflurane at anesthetic concentrations depressed Nav currents and action potential amplitudes. Isoflurane at sub-anesthetic concentrations depolarized resting membrane potential (RMP) of neurons, whereas hyperpolarized the RMP at anesthetic concentrations. Isoflurane at low concentrations induced hyperactivity in vivo, which was diminished in NALCN knockdown mice. In conclusion, enhancement of NALCN by isoflurane contributes to its bidirectional modulation of neuronal excitability and the hyperactivity during induction. [Display omitted] •Volatile anesthetic isoflurane exerts bidirectional modulation of neuronal excitability•Isoflurane enhances NALCN conductance at sub-anesthetic concentration•NALCN knockdown diminishes behavioral hyperactivity during isoflurane induction Anesthesiology; Neuroscience